Culture and identification of a "Deltamicron" SARS‐CoV‐2 in a three cases cluster in southern France. Issue 8 (6th May 2022) - Colson, Philippe; Fournier, Pierre‐Edouard; Delerce, Jeremy; Million, Matthieu; Bedotto, Marielle; Houhamdi, Linda; Yahi, Nouara; Bayette, Jeremy; Levasseur, Anthony; Fantini, Jacques; Raoult, Didier; La Scola, Bernard
Abstract: Multiple SARS‐CoV‐2 variants have successively, or concomitantly spread worldwide since the summer of 2020. A few co‐infections with different variants were reported and genetic recombinations, common among coronaviruses, were reported or suspected based on co‐detection of signature mutations of different variants in a given genome. Here we report three infections in southern France with a Delta 21J_AY.4‐Omicron 21K/BA.1 "Deltamicron" recombinant. The hybrid genome harbors signature mutations of the two lineages, supported by a mean sequencing depth of 1163–1421 reads and a mean nucleotide diversity of 0.1%–0.6%. It is composed of the near full‐length spike gene (from codons 156–179) of an Omicron 21K/BA.1 variant in a Delta 21J/AY.4 lineage backbone. Importantly, we cultured an isolate of this recombinant and sequenced its genome. It was observed by scanning electron microscopy. As it is misidentified with current variant screening quantitative polymerase chain reaction (qPCR), we designed and implemented for routine diagnosis a specific duplex qPCR. Finally, structural analysis of the recombinant spike suggested its hybrid content could optimize viral binding to the host cell membrane. These findings prompt further studies of the virological, epidemiological, and clinical features of this recombinant.